You cannot ablate the Lernaean Hydra: SCN5A mutation in a patient with multifocal ectopic Purkinje-related premature contractions syndrome treated with Flecainide and an implant of a subcutaneous defibrillator—a case report. Issue 4 (30th April 2021) - Leventopoulos, Georgios; Perperis, Angelos; Karelas, Dimitrios; Almpanis, Georgios
Abstract: Background: SCN5A mutations may present with different clinical phenotypes such as Brugada syndrome, long QT3 syndrome, sick sinus syndrome, atrial fibrillation, dilated cardiomyopathy, and the least known multifocal ectopic Purkinje-related premature contractions syndrome. Case summary: We report a case of a 29-year-old woman with palpitations due to multifocal premature ventricular complexes (PVCs) and a family history of sudden death. The previous electrophysiological study had shown that PVCs arose from Purkinje fibres but catheter ablation was unsuccessful. Cardiac magnetic resonance (CMR) imaging demonstrated non-ischaemic areas of subendocardial fibrosis at multiple left ventricular (LV) segments with concomitant dilatation and mild systolic impairment. Amiodarone suppressed the ectopy but caused hyperthyroidism. Due to recent pregnancy, she received no antiarrhythmics which resulted in PVC burden increase and further deterioration of the ejection fraction (EF). After gestation, amiodarone was reinitiated and switched to flecainide after implantation of a subcutaneous defibrillator as a safety net. At follow-up, LV function had almost normalized. Genetic analysis confirmed an SCN5A mutation. Discussion: Multifocal ectopic Purkinje-related premature contractions syndrome is associated with SCN5A mutation which in our case (R222Q) is the most common described. Flecainide can be an appropriate treatment option when ablation is ineffective. Defibrillator—even a subcutaneous type—could be implanted in cases of LV dysfunction or scar. PVCs suppression by flecainide and restoration of EF implies an arrhythmia—induced mechanism of LV impairment.